A Comprehensive Communication Approach to Navigate the Crisis Caused by Online Gambling: Insights from Kemencast #44 on Youtube - Chamil, Andika Yulianto; Djuanda, Safiera Amanda; Septaviana, Nurina (Yayasan Ilomata, 2024)
The COVID-19 pandemic has presented serious challenges to people's mental health, with increasing cases of online gambling addiction being of particular concern. Kemencast YouTube content case study #44 illustrates the complexity of online gambling addiction during the pandemic. This research aims to explore this by focusing on the trigger factors, impacts, and comprehensive communication approaches in dealing with mental health crises related to online gambling addiction. The research method used is qualitative by collecting data through content analysis of a podcast entitled